The effect of linseed oil supplementation on performance, fatty acid composition and oxidative status of rabbits - Trebušak, Tina (Acta agriculturae Slovenica, 2011)
The objective of the present study was to determine the effect of linseed oil supplementation on performance, fatty acid composition and oxidative status of rabbits. Twelve male SIKA rabbits were divided into two groups. The control group (n = 4) received commercial diet and the linseed group (n = 8) received commercial diet containing 9% of linseed oil, which was sprayed onto the pellet. Rabbits were slaughtered at 115 days of age, 52 dazs after the start of the experiment. Live weight, weight gain, feed intake and feed efficiency were recorded. The fatty acid composition of muscle, adipose tissue and liver was determined by the in situ transesterification method and gas chromatography-flame ionisation detection (GC-FID). In order to evaluate the oxidative status of rabbits, the malondialdehyde (MDA) concentration in plasma, liver and muscle were measured. The results show that it is possible to enhance proportion of n-3 polyunsaturated fatty acids (PUFA) in rabbit's muscle, adipose tissue and liver by adding linseed oil in the diet without detrimental effect on productive performance. Linseed oil addition improved fatty acid composition in all tissues by increased PUFA proportion and decreased proportion of saturated and monounsaturated fatty acid. Linseed oil also reduced n-6/n-3 PUFA ratio in all tissues. However, linseed oil addition led to significantly higher MDA concentrations in plasma, liver and muscle. Since PUFA are highlz susceptible to oxidation, further research is needed to focus on protecting animal and their products from lipid oxidation by adding various natural antioxidants to the diet.
Keywords: kinci; rabbits; animal nutrition; prehrana živali; feed additives; krmni dodatki; laneno olje; linseed oil; maščobnokislinska sestava; fatty acid composition; oksidacijski status; oxidative status; performance; proizvodne lastnosti